Implementation of Integrated Science Learning Model Using the Webbed Type: A Systematic Literature Review - Jemeo, Maria Kurniati; Sutadji, Eddy; Pristiani, Riska; Rahayuningsih, Sri (Indonesian Journal of Educational Research and Review, 2024)
Improving the quality of science education in schools remains a critical focus in finding effective teaching models that can integrate various disciplines. The challenges faced is the lack of student engagement in connecting scientific concepts with real-life contexts, as well as low levels of critical thinking and deep understanding of concepts. This study aims to analyze and evaluate the effectiveness of the webbed integrated science teaching model and to explore its impact on students' ability to relate scientific knowledge to real-life contexts. This research employed the systematic literature review (SLR) method. This method is used by collecting and evaluating relevant research on a specific focus topic. Data collected and analyzed from 30 scholarly articles. The research instrument used is a literature assessment sheet. The data analysis technique employed is thematic analysis. The results of this study indicate that the application of the webbed integrated science teaching model has significant potential in enhancing the quality of science education. This model helps students connect information from various disciplines to real-life contexts.